Homework Help: Problem simplifying an equation

1. Aug 18, 2008

mr.t

1. The problem statement, all variables and given/known data
What is the steps between the two equations?

2. Relevant equations
$$P = a^{2}P+b^{2}P^{2}/(P+1) \Rightarrow P^{2}-(a^{2}+b^{2}-1)P-b^{2} = 0$$

Thanks!

2. Aug 18, 2008

tiny-tim

Hi mr.t!

i] put the a2P on the left

ii] multiply both sides by (P + 1)

3. Aug 18, 2008

mr.t

Hello Tiny-tim!
Putting the $$a^{2}P$$ to the left and multiply both sides with (P+1) gives:

$$(P+1)(P-a^{2}P) = b^{2}P^{2} \Rightarrow$$
$$\Rightarrow P^{2}-a^{2}P^{2}+P-a^{2}P-b^{2}P^{2} = 0 \Rightarrow$$
$$\Rightarrow P^{2}(1-a^{2}-b^{2})+P(1-a^{2}) = 0$$

But I still can't come to the final solution? :S

4. Aug 18, 2008

Defennder

I don't think the two steps are equivalent. Let b=0, then a^2=1 if $$P \neq 0$$. Substituting these into the second equation, we have a^2 = 1 only if $$P = 0$$

5. Aug 18, 2008

mr.t

It could be an error in the solution then :grumpy: no fun try to learn stuff when you end up spending your time figuring out the imposible...